Evaluation of Success Rate of Exogenous Obesity Management with an Intensive Follow-up Program - Gül Şeker (Trends in Pediatrics, 2021)
Objective: Obesity critically affects the quality and expectancy of life with its physiological, hormonal, metabolic, and social aspects. This study has assessed the success rate of exogenous obesity management consisting of lifestyle changes with an intensive follow-up in prepubertal children.